2013
DOI: 10.4161/viru.27103
|View full text |Cite
|
Sign up to set email alerts
|

The complex link between influenza and severe sepsis

Abstract: Severe sepsis is traditionally associated with bacterial diseases. While fungi and parasites can also cause sepsis, they are significantly less common than bacterial causes. However, viruses are becoming a growing cause of severe sepsis worldwide. Among these viruses, influenza is crossing all geographic boundaries and is causing larger epidemics and pandemics. As a consequence, more critically ill patients with severe sepsis caused directly by influenza viruses, or indirectly by influenza-induced secondary ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 91 publications
(133 reference statements)
1
49
0
4
Order By: Relevance
“…Our mortality estimates are likely underestimates of true burden of influenza mortality. The survey may have missed deaths, especially among infants who may have presented with sepsis rather than respiratory symptoms . Even among adults, it is possible that they had an underlying illness that made it difficult to classify as ARI through a community survey.…”
Section: Discussionmentioning
confidence: 99%
“…Our mortality estimates are likely underestimates of true burden of influenza mortality. The survey may have missed deaths, especially among infants who may have presented with sepsis rather than respiratory symptoms . Even among adults, it is possible that they had an underlying illness that made it difficult to classify as ARI through a community survey.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to influenza shares many common pathways with the response to bacteria, thus it should not be surprising that an influenza virus infection can have a very similar clinical presentation to bacterial sepsis [9,47,48]. Specifically, several studies have demonstrated that both Toll-like receptors 2 and 4, which are the main receptors for Gram-positive and Gramnegative bacteria, are also related to influenza pathogenicity [49][50][51].…”
Section: Influenza Presenting As Sepsismentioning
confidence: 99%
“…A common and severe complication of sepsis is renal insufficiency. Impaired renal function accentuates the pathogenesis of sepsis through the loss of metabolic, fluid, and electrolyte homeostasis (Hotchkiss et al, 2013;Florescu and Kalil, 2014), and the development of kidney dysfunction doubles the risk for mortality in septic patients (Boomer et al, 2014). Bacterial sepsis and acute endotoxemia induce a number of defects, but the underlying mechanisms remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%